2022
DOI: 10.3389/fnhum.2022.875249
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory action planning for stepping onto competing potential targets

Abstract: The brain plans an anticipatory action for performing tasks successfully and effortlessly even if there are multiple possible options. There is increasing evidence that, when multiple actions are possible, the brain considers two factors when planning an anticipatory action—the probabilistic value and the action cost for each potential action. When the action involves maintaining upright balance, such as standing, stepping, or walking, the action cost for maintaining postural stability could be considered domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
4
1
0
Order By: Relevance
“…The fact that this redistribution occurs hundreds of milliseconds before the start of a head sweep suggests that it may be part of an active preparatory behaviour, as opposed to a biomechanical consequence of the behaviour itself. Similar types of preparatory behaviours involving redistribution of body mass have been observed in caterpillars before cantilevering behaviours (Lin et al, 2011), adult flies during fast escape behaviours (Card & Dickinson, 2008) and humans during stepping (Watanabe & Higuchi, 2022). In addition to redistributing body mass to regions in between protopodia, we also observed unexpected tripod-shaped transient substrate interactions in posterior terminal regions of larvae immediately before forward waves and headsweeps.…”
Section: Erism-warp Allows Computation Of Ground Reaction Forces In D...supporting
confidence: 80%
See 1 more Smart Citation
“…The fact that this redistribution occurs hundreds of milliseconds before the start of a head sweep suggests that it may be part of an active preparatory behaviour, as opposed to a biomechanical consequence of the behaviour itself. Similar types of preparatory behaviours involving redistribution of body mass have been observed in caterpillars before cantilevering behaviours (Lin et al, 2011), adult flies during fast escape behaviours (Card & Dickinson, 2008) and humans during stepping (Watanabe & Higuchi, 2022). In addition to redistributing body mass to regions in between protopodia, we also observed unexpected tripod-shaped transient substrate interactions in posterior terminal regions of larvae immediately before forward waves and headsweeps.…”
Section: Erism-warp Allows Computation Of Ground Reaction Forces In D...supporting
confidence: 80%
“…This redistribution occurs hundreds of milliseconds before the start of a head sweep, suggesting that it may be part of an active preparatory behaviour. Similar preparatory behaviours have been observed in caterpillars before cantilevering behaviours (Lin et al, 2011), adult flies during fast escape behaviours (Card & Dickinson, 2008) and humans during stepping (Watanabe & Higuchi, 2022).…”
Section: Erism-warp Allows Computation Of Ground Reaction Forces In D...supporting
confidence: 74%
“…This redistribution occurs hundreds of milliseconds before the start of a headsweep, suggesting that it may be part of an active preparatory behaviour. Similar preparatory behaviours have been observed in caterpillars before cantilevering behaviours ( Lin et al, 2011 ), adult flies during fast escape behaviours ( Card and Dickinson, 2008 ), and humans during stepping ( Watanabe and Higuchi, 2022 ). More detailed characterisation of this behaviour remains a challenge owing to the changing position of the mouth hooks.…”
Section: Discussionsupporting
confidence: 65%
“…It is noteworthy that these age-related changes were more pronounced in the sagittal plane. Furthermore, although both age groups increased angular momentum with increasing speed during stepping, the age-related changes previously observed at spontaneous speed were exacerbated at faster speeds [21]. Taken together, these results suggest that the greater variation in angular momentum with age and speed generates larger values of angular momentum derivatives and consequently contributes to increasing the distance between the COM and the MMA.…”
Section: Introductionsupporting
confidence: 48%
“…In this context, some authors recently studied instability during stepping. Using the COP trajectory, Watanabe and Higuchi [21] demonstrated that action costs for maintaining postural stability are considered dominantly for planning the stepping. The margin of stability [22] was also analyzed during stepping in different situations, and the higher risk of falls in frail individuals such as older adults were highlighted.…”
Section: Introductionmentioning
confidence: 99%